3(4d+1)-9d=6(-2m+5)-4

Simple and best practice solution for 3(4d+1)-9d=6(-2m+5)-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(4d+1)-9d=6(-2m+5)-4 equation:


Simplifying
3(4d + 1) + -9d = 6(-2m + 5) + -4

Reorder the terms:
3(1 + 4d) + -9d = 6(-2m + 5) + -4
(1 * 3 + 4d * 3) + -9d = 6(-2m + 5) + -4
(3 + 12d) + -9d = 6(-2m + 5) + -4

Combine like terms: 12d + -9d = 3d
3 + 3d = 6(-2m + 5) + -4

Reorder the terms:
3 + 3d = 6(5 + -2m) + -4
3 + 3d = (5 * 6 + -2m * 6) + -4
3 + 3d = (30 + -12m) + -4

Reorder the terms:
3 + 3d = 30 + -4 + -12m

Combine like terms: 30 + -4 = 26
3 + 3d = 26 + -12m

Solving
3 + 3d = 26 + -12m

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 3d = 26 + -3 + -12m

Combine like terms: 3 + -3 = 0
0 + 3d = 26 + -3 + -12m
3d = 26 + -3 + -12m

Combine like terms: 26 + -3 = 23
3d = 23 + -12m

Divide each side by '3'.
d = 7.666666667 + -4m

Simplifying
d = 7.666666667 + -4m

See similar equations:

| x-(2x+3)=-4 | | 2x^3+7x^2-7x-30=0 | | 2w+2(6w-6)= | | 5+3x=5x+7 | | 60=4(6r+3) | | Z-4.3=1.6 | | x+(3x+11)=3 | | (11x-1)+(5y-5)=180 | | -12x+8y=-12 | | -22x+9x= | | 8.3z=4.1z+10.2 | | 0.128-0.035v=0.072v+0.235 | | 6x-x=3x+30 | | 15=5d-5 | | 44-(-b)=76 | | 5x-3+7-8x=19 | | (T)=t^2+100t | | 5z+2=3iz+4i | | wx+b=yforx | | 6c-8=4c | | x+2=-6+72 | | 8x-2=x+4 | | v^2=37 | | 4-9=-13 | | f(x)=0.6+2.75 | | 2a-1=18 | | 4=m/7+5 | | 5n=-3n | | v^3=37 | | 4(x-4)+8=12 | | 2(x+4)+3=15 | | 55=x-48 |

Equations solver categories